2009
DOI: 10.1002/nau.20709
|View full text |Cite|
|
Sign up to set email alerts
|

The impact of female urinary incontinence and urgency on quality of life and partner relationship

Abstract: Female urinary incontinence, urgency and frequency significantly impair the quality of life in both younger and older women, and also have negative effects on the partner relationship and the partner's life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 18 publications
0
18
0
2
Order By: Relevance
“…It is not surprising that women in the normal BMD group were more impacted by pelvic floor symptoms as they were younger and may have an increased activity level such that these symptoms may have more impact. [27] Indeed, the difference in incontinence frequency and volume in the entire cohort were no longer significant once risk factors were controlled for by multivariable analysis. Being able to control for activity level may be an important issue to assess in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…It is not surprising that women in the normal BMD group were more impacted by pelvic floor symptoms as they were younger and may have an increased activity level such that these symptoms may have more impact. [27] Indeed, the difference in incontinence frequency and volume in the entire cohort were no longer significant once risk factors were controlled for by multivariable analysis. Being able to control for activity level may be an important issue to assess in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers who investigated midlife women's perceptions of the effect of managing symptoms of chronic UI found recurring themes of lowered self-esteem (Nicolson, Kopp, Chapple, & Kelleher, 2008), feeling unfeminine (Coyne et al, 2007), and feeling unattractive (Nilsson, Lalos, & Lalos, 2009). Women reported that one of the major goals for seeking incontinence-related surgery was to improve body image and thereby restore confidence in their bodies.…”
Section: Background and Significancementioning
confidence: 99%
“…The negative impact of all types of urinary incontinence on female quality of life and, in particular, social, physical, psychological, occupational and sexual domains, have been extensively reported by several studies conducted in different populations, 1,2 hence the need for proper evaluation and treatment of this condition.…”
Section: Introductionmentioning
confidence: 99%